The earlier, the better? Diagnostic experiences of parents in a community-based early intervention system for preschool children with autism. (April 2019) - Iwasa, Mitsuaki; Shimizu, Yasuo; Hara, Ikuko; Imai, Miho; Honda, Hideo
Background and aims: In many countries, early detection and diagnosis of autism spectrum disorder is largely dependent on parents' initial concern with early symptoms of autism spectrum disorder. Previous research on parental perceptions of the autism spectrum disorder diagnostic process indicates that parental satisfaction may be due to either the timing of the diagnostic notification or the provision of post-diagnostic support. The objective of this research is to study the diagnostic notification process and its impact on parents who are informed of their young child's diagnosis before they notice a problem and whose child undergoes early intervention therapy. Methods: Eighty parents of preschool children diagnosed and undergoing early intervention for autism were surveyed to examine their experience of the diagnostic disclosure process. Results: Of 68 respondents, 39 (58.2%) approved of the timing of diagnostic notification, while 10 of 13 dissatisfied respondents indicated that the diagnosis was communicated too late. However, there was no correlation between a higher degree of parental satisfaction with the diagnostic notification process and earlier timing of notification. Conclusions: Although it is preferable to communicate a diagnosis of childhood autism as soon as possible, findings suggest that a highly individualized approach, allowing a degree of latitude in the timing of notification, may be permissible, depending on the individual case and parental readiness to receive the diagnosis. Implications: Findings have clinical implications related to the concept of optimality of diagnostic disclosure as related to the diagnostic notification process, though later notification tends to lead to more dissatisfaction.